Esquizografias infantis entre as relações de gêneros no espaçotempo da escola - Souza, Edilma de (2022)
Between the bonds and dramas of childhood events, which swarm the school's space-time, multiplicities of affections and sensibilities are experienced that touch and allow themselves to be touched by the sayings, feelings and know-how that swarm with ordinary life. In education, there are discourses that hover over child protagonism and their problematization becomes necessary, because from the experiences felt on the skin in the classroom, it is observed that there are words, actions and gestures that propagate homogenization, normativity and phallogocentrism as deterministic processes and present in the objectification of children's subjectivities. Regarding the research, the presence of phallogocentrism in the space-time of the school was problematized in the observance of understanding: How do children reverberate acts of gender performativities between binary and heteronormative discourses in the context of their school experiences? In this bet, from the thought in/from difference, the research went through the labyrinths of inscriptions in the daily life of a public school in the state network in the interior of the state of Mato Grosso among children who attended the fifth year of elementary school. With the objective of finding, in the direction of other non-customary flows and practices, the enunciations of words and speeches that intend to subvert some imposed standards arising from the order of phallocentric governmentality, as well as child-inventive displacements. The investigative path of the research was followed by the Dramatization method, proposed by Deleuze in the work The Desert Island and Other Texts (2006), this is an exercise in philosophical thinking, having as procedures: reading, understanding, analysis and production of thought, which were explained in the text through children's writing, resulting in schizographies. Schizographies are designated as a subversive writing in the possibility of experiencing other (im)possibles, lines of escape and resistance to the orders of discourses that try to oppress life at all times. Therefore, in this investiture, the children participated in transcreation workshops, through short films, in which the children watched, problematized and produced written-readings of their thoughts. Through schizographies, children asserted themselves as craftsmen of an inventive life, as well as taking on the existing revolutionary character by profaning the norm, the form, the formal and the normal. Considering the scriptural movement of schizographies, it was possible to consider how this minority act resists the forms of domestication and control of child souls, presenting the immanent possibility of becoming-child, the potentiality of childhood novelty in the school curriculum, as other ways were created and barriers were broken to show that in the curriculum there is the possibility of profanation, invention, modification and the improvisation of other (im)possibles in respect to the alterities that inhabit the school.